Bird Species Diversity in the Padawan Limestone Area, Sarawak - Mohammad Saiful, Mansor; Shahrul Anuar, Mohd Sah; Lim, Chan Koon; Mustafa, Abdul Rahman (Universiti Sains Malaysia, 2011)
Bird surveys were conducted in the Padawan Limestone Area for seven days at each of two study sites, Giam and Danu, from August to December 2008. The purpose of the study was to compare the area’s bird species richness and abundance of bird species in other limestone areas and in other forest types. The study also compared the species richness and relative abundance of birds in undisturbed and disturbed areas at both study sites. Twenty mist nets were deployed for 12 hours daily. During this study period, direct observations of birds were also made. In all, 80 species from 34 families were recorded at both sites. At Giam, 120 birds were mist-netted. These birds represented 31 species from 16 families. The direct observations at Giam recorded 13 species from 11 families. In the undisturbed area, 21 species from 13 families were mist-netted, whereas in the disturbed area, 21 species from 10 families were mist-netted. In Danu, a total of 48 birds, representing 25 species from 12 families, were mist-netted. The observations at Danu recorded 34 species from 19 families. Twelve species from 7 families were mist-netted in the undisturbed area, whereas 18 species from 11 families were mist-netted in the disturbed area. Statistical analysis showed that the species diversity index differed significantly between undisturbed and disturbed areas.